92 NOVEL MECHANISMS IN DIABETIC NEUROPATHY: AUTOANTIBODY, FAS-DEPENDENT ACTIVATION OF AUTOPHAGY, APOPTOSIS AND NON-APOPTOSIS CELL DEATH. (1st March 2005) - Towns, R.; Guo, C.; Shangguan, Y.; Hong, S.; Song, I.; Yoshimori, T.; Wiley, J. W.
Abstract : Background: We reported previously that diabetic neuropathy is associated with mitochondrial dysfunction and that sera from type 2 diabetic patients with neuropathy induces complement-independent apoptosis in cultured human neuroblastoma (SY5Y) neurons. Mitochondrial dysfunction is associated with engulfment of the injured organelles in autophagosomes, e.g. autophagy. We hypothesized that sera from type 2 diabetic patients with neuropathy would induce autoantibody-mediated, Fas-dependent activation of autophagy and cell death in SY5Y neurons. Methods: Complement-inactivated sera were obtained from 12 patients with type 2 diabetes and neuropathy (D + N), 6 DM patients without neuropathy (D - N) and 6 healthy age- and gender-matched controls (C). IgG and IgM autoantibody binding to the cell surface was detected using specific FITC-tagged antibodies. Immunoglobulins (Igs) were removed from sera with protein L agrose beads. Fas activation was monitored using Northern and Western detection of Fas and Fas-activated Death Domain (FADD) ± gene silencing with si-FADD. Autophagy was measured using Western and immunofluoresence (IF) detection of the specific marker for autophagosomes, LC3 and mitochondrial colocalization with MitoTracker. Apoptosis was measured by activated caspase-3 and TUNEL assays. Oncosis was measured by mu-calpain immunoreactivity. Results: Sera from the D + N subjects but not D - N or C demonstrated significant increase in IgG and IgM autoantibodies. These sera induced a marked increased in Fas and FADD immunoreactivity detected by Western and IF methods after 2 hours treatment and a parallel increase in autophagy associated with engulfment of mitochondria compared to sera from DM - N subjects and C. Treatment with purified Fas ligand (10 ng/mL) produced similar results at 2 h. After 24 hours treatment with D + N sera there was a significant increase in apoptosis (1.6 ± 0.3%) and oncosis (2.5 ± 0.4%) compared to D - N (0.4 ± 0.2, p<0.05). Treatment with si-FADD reduced D + N induction of FADD and autophagy by 72 ± 8% (p<0.01) and decreased the induction of apoptosis by 48 ± 8% (p<0.05). Induction of Fas, FADD, autophagy, apoptosis and oncosis were absent after removal of Igs. Summary: These results suggest that autoimmune, Fas-dependent activation of autophagy and cell death participate in the pathophysiology of diabetic neuropathy.